Biochar supported photocatalyst (mangrove biochar-TiO2) for organic pollutants removal via synergetic adsorption-photocatalytic process - Ariyanti, Dessy; Azizah, Nadya Ummi; Lesdantina, Dina; Saputra, Erwan Adi; Srivastava, Vimal Chandra (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Access to clean water remains a global challenge, which is made worse by the contamination of chemical dyes. The recent innovations of wastewater treatment have been introduced, such as combined biochar with TiO2 photocatalyst. This study proposed to degrade mainly organic pollutants from dyed wastewater using adsorption-photocatalytic of biochar-supported photocatalyst TiO2 (BSP). Mangroves were converted into biochar via hydrothermal carbonization process and combined with TiO2 by a sol-gel method. The composite was then characterized by SEM-EDX, FTIR, and XRD. The degradation performance of the BSPs was optimized with the addition of Titanium (IV) Isopropoxide (TTIP) solution in biochar for 15-25 mL, solution photocatalyst dosage 0.5–1 g/L, initial dyed water concentration at 10 ppm, pH 5.2, and UV-irradiation time from 30 to 240 min in a photocatalytic reactor. The phenomenon of organic pollutants removal was observed based upon the mechanism and dominance of the process and the degradation reaction rate of organic pollutants in dyed wastewater. Methylene blue used as a model dye was degraded 100% through the adsorption-photocatalysis process using BSP. The highest effective degradation performance was found in BSP 20 that had a functional group area of 4.39923 m²/g, a catalyst loading of 0.5 g/L, and the highest degradation rate at k = 0.021 min?¹. In subsequent development, the synergistic interaction between biochar and TiO2 presents a promising avenue for the development of advanced wastewater treatment systems targeting the removal of organic pollutants, particularly in textile industry.